2022
DOI: 10.1002/slct.202200588
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐Sensitive Carbon Dots Derived from Naphthalenediol for Solvent Polarity Indicator and Anti‐Counterfeiting

Abstract: Herein, a novel type of environment-sensitive carbon dots (ES-CDs) has been synthesized via ethanothermal reaction using 1,6-naphthalenediol as a carbon source and sulfuric acid as a catalyst. The morphology and structure of ES-CDs are characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectra (XPS). ES-CDs exhibit green and excitation wavelength independent emission in different solvents. Using the optical response of ES-CDs towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
(92 reference statements)
1
2
0
Order By: Relevance
“…Based on what is mentioned above, it can easily concluded that the reason for the multicolor CDs may be the size effect. The phenomenon is also verified by the report of Yang et al 13 Figure 2d−f exhibits the corresponding HRTEM images of the CDs, which obviously possess fringe spacings (0.235, 0.240, 0.254 nm) fitting with the (100) lattice distance of graphite carbon. 47,48 This implies that WLS occupied an important position because of its high carbon content of 42.29%.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Based on what is mentioned above, it can easily concluded that the reason for the multicolor CDs may be the size effect. The phenomenon is also verified by the report of Yang et al 13 Figure 2d−f exhibits the corresponding HRTEM images of the CDs, which obviously possess fringe spacings (0.235, 0.240, 0.254 nm) fitting with the (100) lattice distance of graphite carbon. 47,48 This implies that WLS occupied an important position because of its high carbon content of 42.29%.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…6−8 With these advantages, CDs have found wide applications, 9 including living cells, 10 heavy metal indicators, 11 latent fingerprint detection, 12 and especially anti-counterfeiting. 12,13 The preparation method of CDs is one of the research hotspots. In recent years, various raw materials have been used to prepare CDs, such as non-biomass materials, including citric acid, 14−16 pyromellitic acid, 17 1,2,4,5-benzenetetramine tetrahydrochloride, 18 triethanolamine, 19 dopamine, 20 etc.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation